Grammatical errors in cadets’ writing during competition: An analysis of what and why - Yozar Firdaus Amrullah; Fatimah Fatimah; Pratama Irwin Talenta; Ulya Himawati; Kurniawati Afifah Liliyana; Rif'atun Hasanah (EduLite: Journal of English Education, Literature and Culture, 2026)
Writing in English poses substantial challenges for vocational school cadets, particularly in maintaining grammatical accuracy under contextual constraints. These difficulties become more pronounced in competitive settings characterized by time pressure, limited opportunities for revision, and heightened cognitive demands. When writing tasks are performed under such conditions, cadets may struggle to organize and express their ideas accurately and coherently. The study aims to identify the types, frequency, and underlying causes of grammatical errors produced by cadets from three study programs at Politeknik Ilmu Pelayaran Semarang during an English writing competition. Employing a descriptive qualitative design, the research applies Dulay’s surface strategy taxonomy and McDowell’s error analysis procedure to examine writing samples collected from sixteen participants. The findings reveal that misinformation was the most dominant error type (73.90%), followed by omission (15.89%), addition (9.98%), and misordering (0.23%). The errors were primarily attributed to intralingual transfer, followed by interlingual transfer, while time constraints during the competition also contributed to the occurrence of errors. These results indicate that internalized but incomplete grammatical knowledge, rather than first-language interference alone, played a central role in the cadets’ performance. These findings can be used for further research and developing English for specific purposes learning materials, especially for improving writing skills related to the scientific fields of sea transportation cadets, whether it be nautical science, marine engineering, or port and shipping management.